Covid-19's impact on the physical environments of people with intellectual disabilities: a systematic literature review - Nur Khaleeda Mohd Kamil,; Aizan Sofia Amin,; Noremy Md Akhir,; Abdul Rahman Ahmad Badayai,; Insyirah Mohd Zambri,; Rosnah Sutan,; Khairul Farhah Khairuddin,; Wan Arnidawati Wan Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2023)
COVID-19 pandemic is a public health issue. From 2019 to 2022, 4.5 million people died from the COVID-19 epidemic. Consequently, COVID-19 has put a significant strain on every single creature in this world. COVID-19 has been associated with lockdown, thus resulting in lockdown related inequities towards most people in this world, with unanticipated consequences for people with disabilities. Building in this debate, this paper aimed to discuss on the impacts of COVID-19 on the physical health of People with Intellectual Disabilities. Based on the Prisma protocol, this systematic literature review examined 28 publications from Web Sources of Science and Scopus.The study identified three themes regarding the impact of COVID-19 on the physical environment of people with intellectual disabilities namely mental health, social isolation, severe health problems, socioeconomic and psychology. This study has significant implications in understanding how PWID are impacted by COVID 19 and urged that early preventative measures should be taken since People with Intellectual Disabilities are considered a vulnerable population, therefore it is crucial to ensure that their health status are sustained.